The awareness and perception of teledentistry among Malaysian dental professionals in universities and private practices - Chu, Seng Boon; Mohd Fitri, Muhammad Haikal Najmi; Azizi, Danish Yusuf (International islamic Universiti Malaysia, 2024)
The unexpected outbreak of COVID-19 has caused the temporary collapse and suspension of dental practices around the world. With the emergence of teledentistry, this incident unwittingly pushes for a revolutionary modification in the usual provision of dental care. The purpose of the study was to determine the level of awareness and perception of teledentistry among university and private-sector dental practitioners. This descriptive cross-sectional study used a pre-validated 27-item questionnaire with a 5-point Likert scale to assess the perceptions of university-based and private dental practitioners regarding teledentistry in four domains: the usefulness of teledentistry for patients, its benefits to dental practices, the potential improvements it can bring to dental practices, and concerns about the adverse effects of teledentistry. 150 dental practitioners participated in the research (30% overall response rate). More than 70% of respondents agreed that teledentistry can benefit both dentists and patients by improving communication and treatment monitoring. However, 45–80% of dentists had doubts regarding the technology's dependability, diagnostic accuracy, and patient data privacy. In conclusion, the results of this study suggest that Malaysian dentists are well-informed and prepared to implement teledentistry in their practices. However, additional research is necessary to determine the viability of commercial usage of teledentistry, both in Malaysia and internationally